Optical trapping of interfaces at ultra-low interfacial tension. - Verhoeff, A; Lavergne, F; Bartolo, D; Aarts, D; Dullens, R (Royal Society of Chemistry, 2015)
We achieve active control of interfacial phenomena by optically trapping the interface using the gradient forces of a strongly focussed laser beam parallel to the interface. We illustrate our technique in a phase separated colloid-polymer mixture by distorting the interface in a very controlled way. The static structure of the manipulated interface as well as its dynamic relaxation behaviour are analysed. Both the statics and dynamics can be related to the capillary wave height-height correlation functions using the fluctuation dissipation theorem up to surprisingly large deformations of the interface. To underline the novelty and potential of our approach we also show multiple interface distortions and the controlled snap-off of liquid droplets.